Conceptual Validation of Project Based Learning in Buffer Solution - Peri Oktiarmi; Muhammad Rusdi; Rayandra Asyhar (PendIPA Journal of Science Education, 2023)
This research was applied to the project learning model of supporting learning materials at high school SMAN 3 Jambi City. The learning model in the 2013 curriculum must fulfill the five steps scientific approach namely Observing, Asking, Experimenting, Collecting data, and Communicating, which is the goal of a learning model like this to make students understand learning well, educational design-based research that adopts the substance of the formative evaluation type with the characteristics of substance experts in procedural assessment, one-on-one evaluation, small group evaluation and field presentation. The concept of formative evaluation can be integrated with research and development method. The Project Based Learning (PjBL) model in Buffer Solution was using a development process type with a hybrid theory-based approach and directing eight-step practice. The theoretical steps are identifying data sources, collecting data and analyzing data, while the practical steps are generating model ideas, describing models, validating concepts and practitioners and formulating recommendations for testing models. The product was validated by a team of experts which includes practitioner validation to see the practicality of using the product being developed. A small group test was carried out to see the application of the product being developed. The results showed that learning chemistry using the PjBL model could increase the activity and results of students' chemistry learning on the concept of buffer solutions. The increase in student chemistry learning outcomes in the buffer solution concept can also be observed based on the value in general of the learning outcomes obtained by students in cycle I of 68.09 increased to 74.81 in cycle II and % completion in the classical way from 39.39 percent increased to 87.88 percent and this fulfills the marker of success is classical completeness reaching 85 percent with Minimum Completeness Criteria of 70.